PARENTING MANAGEMENT BASED ON PRAYER THERAPY: A HOLISTIC APPROACH TO OVERCOMING THE INNER CHILD AT THE AL AMIN CIAMIS ISLAMIC BOARDING SCHOOL - Nurjaman, Irman; Muflihun, Muflihun; Ihsanda, Nu Man; Aridin, Bambang Samsul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research examines parenting management based on prayer therapy as a holistic approach to overcoming the inner child at Pesantren Al Amin Ciamis. The main objective of this research is to explore the effectiveness of prayer therapy in supporting the emotional healing of santri affected by the inner child. The methodology used is a qualitative approach, with data collection through in-depth interviews, participatory observation, and document analysis related to parenting practices in pesantren. Data analysis was conducted using thematic analysis techniques to identify patterns and relationships between the practice of prayer therapy and the emotional development of santri. The findings show that prayer therapy significantly contributes to increasing self-awareness, reducing anxiety, and improving santri's interpersonal relationships. Santris who attended prayer therapy sessions reported feeling calmer and better able to deal with emotional challenges. This holistic approach also strengthens the integration between spiritual and educational aspects, creating an environment that supports the overall growth of the santris. This research provides important insights into the implementation of parenting management based on prayer therapy in pesantren, the types of prayer used in therapy, and its impact on the character development of santri. Thus, it is hoped that this model can be a reference for other educational institutions in overcoming inner child problems through a more comprehensive approach